2017
DOI: 10.3126/jnhrc.v15i1.18011
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice Regarding Pharmacovigilance and Consumer Pharmacovigilance among Consumers at Lalitpur District, Nepal

Abstract: Background: Adverse drug reactions (ADRs) can be a big threat to the health of people in Nepal as a variety of medicines are consumed in the country. Involving consumers in pharmacovigilance can strengthen ADR reporting. The study aims to find out knowledge, attitude and practice regarding pharmacovigilance and consumer pharmacovigilance among consumers at Lalitpur district, NepalMethods: It was carried out in outpatients visiting in KIST Medical College and Teaching Hospital, Lalitpur, Nepal. Participant’s kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Several studies in Nepal have reported that HCPs have a lack of knowledge regarding the PV before any kind of educational intervention [14,15,17,19,20]. Few studies, however, conducted in Nepal to assess the outcomes of an educational intervention to increase KAP of HCPs [21][22][23]. Educational intervention, interactive sessions and multifaceted continuous medical education support knowledge and behavioral changes in health professionals [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in Nepal have reported that HCPs have a lack of knowledge regarding the PV before any kind of educational intervention [14,15,17,19,20]. Few studies, however, conducted in Nepal to assess the outcomes of an educational intervention to increase KAP of HCPs [21][22][23]. Educational intervention, interactive sessions and multifaceted continuous medical education support knowledge and behavioral changes in health professionals [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Other challenges faced by developing countries include excessive workload, lack of expertise and funding, weak regulations, low literacy levels, use of counterfeit drugs, and self-medication (Alshammari and Alshakka, 2014;Shrestha and Bhandari, 2013). The majority of respondents considered consumer pharmacovigilance necessary and this concurs with the responses of a survey conducted among consumers in Lalitpur, Nepal (Jha et al, 2017). Professionals from WHO, UMC and pharmacovigilance centers in the Netherlands and the UK considered patient reporting to be the future of pharmacovigilance (Inácio et al, 2018).…”
Section: Discussionmentioning
confidence: 55%
“…Most respondents believed that HCPs should inform the public (patients) about ADRs using detailed information. Many studies [48][49][50][51][52] have shown that HCPs are the main source of ADR-related knowledge for patients, while patients receive insufficient information about drug ADRs from HCPs, and many patients think that cooperation among HCPs is insufficient and cannot guarantee that they receive enough information about ADRs. This emphasizes the fact that medical workers must improve communication with the public by actively explaining to patients the importance of ADRs, monitoring, and reporting.…”
Section: Discussionmentioning
confidence: 99%